Dombey and Son - Dickens, Charles (London Everyman's Library, 1994)
Introduction "Dombey and Son" is a novel by Charles Dickens, first published in monthly parts between 1846 and 1848. The full title is "Dealings with the Firm of Dombey and Son: Wholesale, Retail and for Exportation." The novel is one of Dickens's major works and highlights the complexities of family relationships and the impact of commercial values on human life. Plot Summary The story revolves around the wealthy and arrogant Paul Dombey, the owner of the shipping company "Dombey and Son." He is obsessed with the idea of having a son to carry on the family business. When his wife gives birth to a son, Paul, and dies shortly after, Dombey is overjoyed with the arrival of his heir, yet remains indifferent to his daughter, Florence. Young Paul is a sickly child, and despite all the attention and resources devoted to him, he dies at a young age, leaving Mr. Dombey devastated. Florence, who longs for her father’s love, is neglected and eventually runs away to escape her harsh treatment at home. Themes "Dombey and Son" explores various themes such as pride, the corrupting influence of money, and the struggle between personal affection and commercial interests. Dickens critiques the materialistic society of Victorian England and the dehumanizing effects of the Industrial Revolution. Through the character of Mr. Dombey, Dickens portrays the destructive power of pride and the importance of emotional connections over financial success. Characters Paul Dombey: The proud and wealthy businessman who dreams of a son to continue his legacy. Florence Dombey: Mr. Dombey’s neglected daughter, who seeks love and affection from her father. Paul Dombey Jr.: The frail and sickly son of Mr. Dombey, whose early death deeply affects his family. Edith Granger: Mr. Dombey’s second wife, who marries him for financial security but despises him. Mr. Toots: A humorous character who is deeply in love with Florence and provides comic relief. Critical Reception "Dombey and Son" was well-received upon its publication and is considered one of Dickens’s more mature works. Critics have praised the novel for its detailed character development, social critique, and emotional depth. The story’s exploration of family dynamics and societal values continues to resonate with readers today. Conclusion "Dombey and Son" is a richly textured novel that offers a poignant look at the intersections of family, commerce, and societal expectations in Victorian England. Dickens's masterful storytelling and vivid character portrayals make this novel a compelling read and a significant work in the canon of English literature.
Keywords: 19th Century British Fiction; English Literature